Its oil becomes soap: a teaching sequence for teaching Environmental Chemistry in technical professional education at mid-level (Research, Society and Development, 2021)
The objective of this work was to develop a didactic sequence for the teaching of environmental chemistry in technical professional education at high school level, having as premises, pedagogical actions and citizen insertion of environmental awareness articulated to the teaching of chemistry. To this end, through a didactic sequence structured in 9 (nine) steps, initially awareness lectures were held on the inappropriate disposal of edible oils, oil collection campaigns, research, analysis, and improvement of soap manufacturing recipes, as well such as the acquisition of equipment and supplies, with a focus on the production of soap for donations to institutions, associations and needy communities. With the development of this work, in addition to enriching the pedagogical practice in a more concrete and socially responsible perspective, it was possible to present to the school community alternatives to the disposal of residual oils, promoting a change in attitude and environmental awareness, especially in the working practices of future technicians in chemistry, the target audience of the proposed didactic sequence. It was also possible to carry out community actions of environmental education and projects involving the school community, resulting in the publication and free distribution of a properly balanced soap recipe book.